Development of Numerical Models to Predict the Compressive Strength of High Strength Concretes Based on Maturity Method - Demir, Tuba; Alyamaç, Kürşat Esat (My University, 2025)
The aim of this study was to develop numerical models to predict the compressive strength of HSCs using Nurse-Saul and Arrhenius (NS-Arr) maturity functions. For this purpose, 9 concrete series with different concrete mix ratios of 400-450-500 kg/m3 binder dosage were produced. Silica fume was used instead of cement at the rate of 5-10-15% by volume and marble powder was used instead of fine aggregate at the rate of 8-10-12% by volume. While the specimens were kept in standard water curing, the temperature values were measured every 5 minutes at the end of the 1st, 3rd, 7th, 14th and 28th days to be used in the maturity test and the results were transferred to the computer. The compressive strength test was also performed in the same time periods. The data obtained from the test results were analyzed and a separate numerical model was developed for each maturity function applied. In addition, with the use of these models, it is thought that concrete compressive strength will be predicted with high accuracy in a short time, the project-work plan will be carried out without loss of time and environmental sustainability will be contributed.
Keywords: Marble powder; compressive strength; silica fume; maturity; High strength concrete